2021
DOI: 10.1007/s42943-021-00032-w
|View full text |Cite
|
Sign up to set email alerts
|

Excellence Through Downstream Innovation in Times of Pandemic: Insights from the Auto Sector

Abstract: The COVID-19 pandemic has disrupted the industrial supply chain globally. The automotive sector in India has also suffered and are trying surviving while reviewing and reinventing business models, structures and processes, to cope with this unprecedented crisis. This study is of an Indian auto OEM major as it focused upon training its downstream partners, to counter a situation of complete lock-down due to the pandemic. The authors attempt to develop a service excellence framework, based upon their unique enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Apply the simple but robust DEMATEL (Agarwal and Kapoor, 2021 and Ojha et al. , 2021) approach for understanding the interrelationships between the enabling factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apply the simple but robust DEMATEL (Agarwal and Kapoor, 2021 and Ojha et al. , 2021) approach for understanding the interrelationships between the enabling factors.…”
Section: Methodsmentioning
confidence: 99%
“…In ISM, the output depicts the driving and dependence power (Kumar et al. , 2017) of each factor, while the output from DEMATEL uncovers the cause and effect relationship (Agarwal and Kapoor, 2021 and Ojha et al. , 2021) and its degree of influence within the set of interacting factors.…”
Section: Methodsmentioning
confidence: 99%
“…DEMATEL, which was originated at the Battelle Memorial Institute's Geneva Research Centre in 1971, was used by the authors since it was found to be useful in analyzing the cause-and-effect relationships among different components of the system Ojha et al. (2021) and Agarwal and Kapoor (2021).…”
Section: Methodsmentioning
confidence: 99%
“…DEMATEL, which was originated at the Battelle Memorial Institute's Geneva Research Centre in 1971, was used by the authors since it was found to be useful in analyzing the causeand-effect relationships among different components of the system Ojha et al (2021) and Agarwal and Kapoor (2021). It was also found by the authors from the literature review that DEMATEL is still not a very popular tool and hence the thought of exploring it in this research.…”
Section: Methodsmentioning
confidence: 99%
“…A robust employee involvement in decision making process is a credible criterion, for enhancing the performance of organizations in the turbulent and competitive market place. Ojha et al (2021) showed interactive marketing and effective communication will continue playing a significant role for service excellence in this constrained physical engagement world of service provider and customer in automotive sector.…”
Section: Quality Performance On Product and Servicementioning
confidence: 99%